ANALYZING THE EFFECTIVENESS BILLINGUAL EDUCATION PROGRAMS IN PROMOTING ENGLISH PROFICIENCY AMONG MULTILINGUAL STUDENTS - Samiyeva Nazokat Olim qizi; Eshonqulova Sarvinoz Yashinovna (TADQIQOTLAR, 2026)
ABSTRACT Bilingual education programs play an important role in supporting English language development among multilingual students. These programs use both the native language and English as mediums of instruction to help learners understand academic content while improving their language skills. This study analyzes the effectiveness of bilingual education programs in promoting English proficiency, focusing on students’ development in reading, writing, speaking, and listening. It also highlights key teaching strategies such as code-switching, translanguaging, and scaffolded instruction that support language learning in bilingual classrooms. The study concludes that well-implemented bilingual education programs can significantly enhance English proficiency and academic performance among multilingual learners.